Pengaruh Kualitas Audit, Debt Ratio, Ukuran Perusahaan, Audit Lag Terhadap Opini Audit Going Concern - Nauval Nadzif; Ngurah Pandji Mertha Agung Durya (Pusat Riset Manajemen Dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia, 2022)
The study aims to determine the effect of audit quality, debt ratio, firm size, and audit lag on going-concern audit opinion. The population in this study is manufacturing companies listed on the Indonesia Stock Exchange from 2017 to 2020. The sample selection uses the purposive sampling method and obtained 492 samples. The sources of data used are secondary data. Debt ratio and audit lag significantly affects audit opinion based on logistic regression analyses using the SPSS 24.0 program. Meanwhile, audit quality and firm size do not affect going concern audit opinion.